An Iterative Model as a Tool in Optimal Allocation of Resources in University Systems - Onanaye, Adeniyi S (International Journal of Engineering and Management Research, 2019)
In this paper, a study was carried out to aid in adequate allocation of resources in the College of Natural Sciences, TYZ University (not real name because of ethical issue). Questionnaires were administered to the highranking officials of one the Colleges, College of Pure and Applied Sciences, to examine how resources were allocated for three consecutive sessions(the sessions were 2009/2010, 2010/2011 and 2011/2012),then used the data gathered and analysed to generate contributory inputs for the three basic outputs (variables)formed for the purpose of the study. These variables are: 1 x represents the quality of graduates produced; 2 x stands for research papers, Seminars, Journals articles etc. published by faculties and 3 x denotes service delivery within the three sessions under study. Simplex Method of Linear Programming was used to solve the model formulated.